Characteristics of plasma streams and optimization of operational regimes for magnetoplasma compressor - Bandura, A.N.; Byrka, O.V.; Garkusha, I.E.; Ladygina, M.S.; Marchenko, A.K.; Petrov, Yu.V.; Solyakov, D.G.; Chebotarev, V.V.; Chuvilo, A.A. (Вопросы атомной науки и техники, 2011)
The main objective of these studies is characterization of dense xenon plasma streams generated by magnetoplasma compressor (MPC) in different operational regimes. Optimization of plasma compression in MPC allows increase of the plasma stream pressure up to 22…25 bar, average temperature of electrons of 10…20 eV and plasma stream velocity varied in the range of (2…9)×10⁶ cm/s depending on operation regime. Spectroscopy measurements demonstrate that in these conditions most of Xe spectral lines are reabsorbed. In the case of known optical thickness, the real value of electron density can be calculated with accounting self-absorption. Estimations of optical thickness were performed and resulting electron density in focus region was evaluated as 10¹⁸ cm⁻³. Remove selected